PIROLISIS SABUT KELAPA (Cocos nucifera L) MENGGUNAKAN INSTRUMEN PYROLYSIS-GAS CHOMATOGRAPHY/MASS SPECTROMETRY (PY-GC/MS) - Afdaliah, Noor; Subagyono, RR Dirgarini Julia Nurlianti; Allo, Veliyana Londong (PROSIDING SEMINAR NASIONAL KIMIA, 2023)
Pyrolysis of a coconut ( Cocos nucifera L ) husk using a pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) instrument was carried out. This research was conducted to determine the chemical composition of pyrolysis of a coconut husk at temperaturs of 350, 450 and 550 °C. Pyrolysis of coconut husk produced lignin derivative products by 15-32% and cellulose/hemicellulose derivative products 9-34%. The gas product produced in the co-pyrolysis of a mixture microalgae anda coconut fiber is 41-50%. Pyrolysis product with the highest % area, namely m ethyl a lcohol , 2- b utanone , p henol , b enzofuran, 2,3-dihydro- dan 2- m ethoxy-4-vinylphenol   Keywords:   Co-pyrolysis, Py-GC/MS dan coconut husk